2015
DOI: 10.5455/2319-2003.ijbcp20150407
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization study in genitourinary infections used as a teaching tool for rational therapy for MBBS students in a Medical College at Dehradun, Uttarakhand

Abstract: Background: There is a need to introduce clinical pharmacology at the undergraduate level in order to improve rational prescribing of medicines. The present study was undertaken to analyze drug utilization pattern of genitourinary infections to teach certain basic skills to MBBS students which will form an integral component of practicing rational therapeutics. Methods: The retrospective study was conducted by Pharmacology Department in Shri Guru Ram Rai Institute of Medical and Health Sciences (SGRRIM and HS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…In the current study it was seen that UTIs were almost equally distributed in both genders whereas in some other studies a higher incidence was seen in women, while yet other studies reported more incidence in men. [11][12][13][14][15] The highest incidence was seen in the age group of 18-30 years, which is similar to that was reported, while other studies reported more incidence in a higher age group. 3,11,16 The commonest causative organism was found to be Escherichia coli which is in concordance with other reports.…”
Section: Discussionsupporting
confidence: 77%
“…In the current study it was seen that UTIs were almost equally distributed in both genders whereas in some other studies a higher incidence was seen in women, while yet other studies reported more incidence in men. [11][12][13][14][15] The highest incidence was seen in the age group of 18-30 years, which is similar to that was reported, while other studies reported more incidence in a higher age group. 3,11,16 The commonest causative organism was found to be Escherichia coli which is in concordance with other reports.…”
Section: Discussionsupporting
confidence: 77%
“…A study reported findings with almost 90% drugs were prescribed by their respective brand name. 37 However a recent retrospective, record-based study recorded a contradictory finding with 98.1% drugs prescribed in generic form in a tertiary care hospital in inpatients with urinary tract infection. 38 Prescribing by generic name needs to be promoted in our hospital to curb drug duplication, medication error and adverse effects due to medication therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO drug use indicators are highly standardized and are recommended for inclusion in drug utilization studies. 8 Antimicrobial resistance is one of the major global preventable problems. The causes of antimicrobial resistance are unnecessary use, inappropriate doses, inadequate duration of therapy and irrational fixed dose drug combinations.…”
Section: Discussionmentioning
confidence: 99%